2021
DOI: 10.1108/rausp-08-2019-0174
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of consumer information search in online and offline environments

Abstract: Purpose The purpose of this study is to identify major themes and potential research opportunities in online and offline consumer search. Design/methodology/approach A systematic review was conducted based on 118 articles identified from prevalent journal databases. Keywords frequency analysis was carried out to identify the major themes. An inductive thematic analysis was carried out to verify the generated themes. Findings Results show that uncertainty, knowledge, perceived risk, price, experience and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 88 publications
(159 reference statements)
1
5
0
Order By: Relevance
“…While buying products, customers face the uncertainty of decision-making and specific information search costs (Haridasan et al , 2021). Consumers do not often envision which products to buy before shopping, especially for goods such as food or beverages.…”
Section: Discussionmentioning
confidence: 99%
“…While buying products, customers face the uncertainty of decision-making and specific information search costs (Haridasan et al , 2021). Consumers do not often envision which products to buy before shopping, especially for goods such as food or beverages.…”
Section: Discussionmentioning
confidence: 99%
“…This argument was later supported in the works of Racherla et al ( 2012) and Lee and Shin (2014), who found out that consumers tend to value product-related messages which are perceived as higher quality [38,39]. In the context of SNSs, as consumers are often overloaded with suggestions and recommendations about their desired products from many information sources, they must use a set of criteria to examine such information [40]. In general, those criteria are in accordance with the receiver9s preferences and demands [41].…”
Section: B Determinants Of Perceived Usefulnessmentioning
confidence: 93%
“…Haridasan, Fernando and Saju [ 22 ] outlined that the search for information by consumers is based on factors such as knowledge of the consumer, price, perceived risk, experience, involvement and uncertainty. In political marketing research such as this, information search by voters (consumers) concerns the knowledge, source of information, availability, experience and involvement.…”
Section: Literature Reviewmentioning
confidence: 99%